In vitro and in silico testing of partially and fully bioresorbable vascular scaffold. (22nd January 2021) - Filipovic, Nenad; Nikolic, Dalibor; Isailovic, Velibor; Milosevic, Miljan; Geroski, Vladimir; Karanasiou, Georgia; Fawdry, Martin; Flanagan, Aiden; Fotiadis, Dimitrios; Kojic, Milos
Abstract: Coronary artery disease (CAD), one of the leading causes of death globally, occurs due to the growth of atherosclerotic plaques in the coronary arteries, causing lesions which restrict the flow of blood to the myocardium. Percutaneous transluminal coronary angioplasty (PTCA), including balloon angioplasty and coronary stent deployment is a standard clinical invasive treatment for CAD. Coronary stents are delivered using a balloon catheter inserted across the lesion. The balloon is inflated to a nominal pressure, opening the occluded artery, deploying the stent and improving the flow of blood to the myocardium. All stent manufacturers have to perform standard in vitro mechanical testing under different physiological conditions. In this study, partially and fully bioresorbable vascular scaffolds (BVS) from Boston Scientific Limited have been examined in vitro and in silico for three different test methods: inflation, radial compression and crush resistance. We formulated a material model for poly-L-lactic acid (PLLA) and implemented it into our in-house software tool. A comparison of the different experimental results is presented in the form of graphs showing displacement-force curves, diameter – load curves or diameter - pressure curves. There is a strong correlation between simulation and real experiments with a coefficient of determination (R 2 ) > 0.99 and a correlation coefficient (R) > 0.99. This preliminary study has shown that in-silico tests can mimic the applicable ISO standards for mechanical in vitro stent testing, providing the opportunity to use data generated using in-silico testing to partially or fully replacing the mechanical testing required for regulatory submission.